2007
DOI: 10.1002/mabi.200700041
|View full text |Cite
|
Sign up to set email alerts
|

Melt Spinning of Bacterial Aliphatic Polyester Using Reactive Extrusion for Improvement of Crystallization

Abstract: This paper reports on an attempt to use reactive extrusion with peroxide as a comfortable pathway for improvement of the crystallization of poly(3-hydroxybutyrate) in a melt spinning process. At first, rheological and thermal properties of the modified melts are determined in order to assess the effect of nucleation. Then spinning tests are carried out. Molecular weights and molecular weight distributions of the spun fibers are determined by chromatographic methods. Average crystallite size is measured by wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, the crystallinity of the neat PHBV or PHB fibers was reported [46,[56][57][58][59] to be ca. 50% or higher.…”
Section: Dsc Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the crystallinity of the neat PHBV or PHB fibers was reported [46,[56][57][58][59] to be ca. 50% or higher.…”
Section: Dsc Resultsmentioning
confidence: 96%
“…This may be due to the rather poor melt-spinnability of PHBV or PHB [46]. Additionally, the PHBV fibers would become rigid and fragile as the secondary crystallization proceeded [46], which made the idea of optimizing PLA fibers with PHBV sound incredible.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…PHB fibers stretched after isothermal crystallization had the oriented a-form crystal with the 2(1) helix conformation and the b-form with the planar zigzag conformation. Vogel et al (2007) attempted to use reactive extrusion with peroxide as a comfortable pathway for improvement of the crystallization of PHB in a melt spinning process. They succeeded in improving the crystallization in the spinline and of the inhibition of the secondary crystallization in the fibers.…”
Section: Pha As Packaging Materialsmentioning
confidence: 99%
“…The results of mechanical testing also revealed that these nucleated fibers are well suited for textile processing, but the method required a large expenditure for manufacturing of the α ‐cyclodextrin/PHB inclusion complexes. The same authors16 also reported on an attempt to use reactive extrusion with peroxide as a convenient pathway for improvement of the crystallization of poly(3‐hydroxybutyrate) in a melt‐spinning process. They found that the crystallization parameters of PHB fibers were dramatically improved by the change of molecular structure as a consequence of reactive extrusion.…”
Section: Introductionmentioning
confidence: 99%